Keragaan Beberapa Galur Jagung Manis (Zea mays L. saccharata) Mutan Generasi M3 Berdasarkan Karakter Morfologi dan Daya Hasilnya. - Muharam; Lukman Ari Wardana; Muhammad Syafi'i (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
Sweet corn (Zea mays L. saccharata) is an agricultural commodity that is very popular with Indonesians, because it tastes sweet and contains high carbohydrates. The need for this commodity continues to increase, but the need for this commodity is not matched by the production produced by farmers. Efforts are needed to increase sweet corn production, one of which is the assembly of superior varieties through plant breeding programs using gamma ray mutation techniques. This study aims to obtain the sweet corn lines with the best morphological appearance in the M3 generation. This experiment was carried out from August to October 2020. The research method used was an experimental method and the design used was a stump factor randomized block design (RBD) consisting of 37 sweet corn lines resulting from gamma ray mutations G1M0, G1M1, G1M3, G2M0, G2M1. , G2M2, G2M3, G3M0, G3M1, G3M2, G3M3, G4M0, G4M1, G4M3, G5M0, G5M1, G5M3, G6M0, G6M1, G6M2, G7M0, G7M1, G7M2, G1M08, G7M2, G1M08, G8M2 , G9M2, G9M3, G9M4, G10M0, G10M1, G10M2, G10M3 and 2 comparator varieties Excotic Pertiwi, and Bonanza F1. Each treatment was repeated 2 times in order to obtain 78 experimental units. The treatment effect was analyzed by analysis of diversity (ANOVA) and if the F test at 5% level is significant, it is necessary to carry out further DMRT (Duncan Multiple Range Test) at the 5% level to determine the best treatment. Based on the results of the study, there was the best treatment on several M3 generation mutant sweet corn lines in the G1M1 line showing the best average yield on plant height of 192,24 cm, 50% flowering age of 39,50 days, the number of cobs planted of 1,50 pieces. , and ear weight per plot of 2,32 kg. Meanwhile, the G10M1 genothype showed the best average yield on the number of leaves of 12,90 sheet. Keywords: genothype, sweet corn, qualitative and quantitative characters.